2022
DOI: 10.1080/1461670x.2022.2052346
|View full text |Cite
|
Sign up to set email alerts
|

Automated News Reading in the Neural Age: Audience Reception and Perceived Credibility of a News Broadcast Read By a Neural Voice

Abstract: Automated journalism is rapidly developing in the news industry. Among the most recent and promising technological potentials are neural voices, i.e. text-to-speech technology powered by neural networks. Based on a reception analysis with in-depth qualitative interviews (N =12), this study explores how Danish radio listeners receive a full news broadcast read by a neural voice and perceive the credibility of the neural reader and the news content. Results show that the participants divide into two types: the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…For instance, the Neurojour project (Heiselberg, 2021) is an innovative pilot project within the field of journalism research that tests psychophysiological measures. In a separate study, participants in both groups (neural voices: textto-speech technology supported by neural networks; and human reporter voices) evaluated "neural news" with particular attention to voice emotion (Heiselberg et al, 2022). And in Heiselberg (2021)'s article, they expressed concern that as AI broadcasts get closer to humans, "The Uncanny Valley" (see Mori et al, 2012) could occur, which is consistent with Clark et al's (2021) earlier research.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…For instance, the Neurojour project (Heiselberg, 2021) is an innovative pilot project within the field of journalism research that tests psychophysiological measures. In a separate study, participants in both groups (neural voices: textto-speech technology supported by neural networks; and human reporter voices) evaluated "neural news" with particular attention to voice emotion (Heiselberg et al, 2022). And in Heiselberg (2021)'s article, they expressed concern that as AI broadcasts get closer to humans, "The Uncanny Valley" (see Mori et al, 2012) could occur, which is consistent with Clark et al's (2021) earlier research.…”
Section: Introductionsupporting
confidence: 58%
“…In other words, Zheng et al 's (2018) experiments revealed that neutral news written or broadcast by AI elicited the same response from audiences as news written or broadcast by human journalists. There are also academics who employ qualitative research techniques (Heiselberg et al, 2022). On the basis of in-depth qualitative interviews, their reception analysis (n = 12) investigated how Danish radio listeners perceive the credibility and news content of neural readers when they hear complete news broadcasts through neural voices.…”
Section: Ai-automated Journalism Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, AI is also extensively adopted in automated journalism for writing and broadcasting (Heiselberg et al, 2022 ). Yet, there has been limited systematic research on the variances in brain activation between human and artificial voices during newscasts.…”
mentioning
confidence: 99%